2014
DOI: 10.1261/rna.043976.113
|View full text |Cite
|
Sign up to set email alerts
|

Predicting structure and stability for RNA complexes with intermolecular loop–loop base-pairing

Abstract: RNA loop-loop interactions are essential for genomic RNA dimerization and regulation of gene expression. In this article, a statistical mechanics-based computational method that predicts the structures and thermodynamic stabilities of RNA complexes with loop-loop kissing interactions is described. The method accounts for the entropy changes for the formation of loop-loop interactions, which is a notable advancement that other computational models have neglected. Benchmark tests with several experimentally vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…This is consistent with previous studies that demonstrated the significant contributions of the loop-closing base pair to the thermal stability of loop-loop kissing interactions in various biological systems such as the kissing complex of TAR-aptamer of HIV [3537], and the RNA I-RNA II complex of ColE1 plasmid [38, 39]. Both H2-CG and H3-CG showed drastic decrease in both thermal and mechanical stability of their kissing complexes, suggesting that the change of 5’A•U3’/5’U•A3’ to 5’C•G3’ may partially disrupt even the conformation of the 5’GACG3’ tetra-loop, making it less optimized for loop-to-loop kissing interactions.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies that demonstrated the significant contributions of the loop-closing base pair to the thermal stability of loop-loop kissing interactions in various biological systems such as the kissing complex of TAR-aptamer of HIV [3537], and the RNA I-RNA II complex of ColE1 plasmid [38, 39]. Both H2-CG and H3-CG showed drastic decrease in both thermal and mechanical stability of their kissing complexes, suggesting that the change of 5’A•U3’/5’U•A3’ to 5’C•G3’ may partially disrupt even the conformation of the 5’GACG3’ tetra-loop, making it less optimized for loop-to-loop kissing interactions.…”
Section: Discussionsupporting
confidence: 93%
“…Chen et al developed a statistical mechanics-based virtual bond lattice model (“Vfold”) to compute the entropy parameters through conformation enumeration for pseudoknotted structures, kissing loops, and RNA-RNA kissing complexes (19, 20, 23, 90). …”
Section: Two-dimensional (2d) Structure Predictionmentioning
confidence: 99%
“…For example, during the mRNA splicing process, RNA/RNA complexes formed by small nuclear RNAs undergo multiple structural rearrangements in the different steps of splicing, 11 microRNAs regulate gene expression by binding to gene targets (at 3′ untranslated regions of target mRNA transcripts), 12 and RNA/RNA dimerization plays essential role in viral replication. 13, 14 Many of the processes of RNA-RNA binding are facilitated by the intermolecular loop-loop interactions between RNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The results led to several predictions for RNA mechanisms, such as pseudoknot-involved conformational switch between bistable secondary structures, 26 microRNA-gene target interactions, 12 and RNA/RNA kissing dimerization in viral replication. 13, 14 …”
Section: Introductionmentioning
confidence: 99%